The Influence of Swelling on Elastic Properties of Polyacrylamide Hydrogels - Subramani, Ramesh; Izquierdo-Alvarez, Alicia; Bhattacharya, Pinaki; Meerts, Mathieu; Moldenaers, Paula; Ramon, Herman; Van Oosterwyck, Hans (Frontiers in Materials, 2020)
Polyacrylamide (PAM) hydrogels are commonly used as substrates for cell mechanical and mechanobiological studies because of their tunable stiffness and ease of handling. The dependence of bulk rheological and local elastic properties (assessed by Atomic Force Microscopy) of PAM hydrogels on its composition and polymerization temperature has been extensively studied. PAM hydrogels swell when immersed in media, but the influence of swelling on local elastic properties is poorly characterized. We report here, for the first time, the direct measurements of volumetric swelling and local elastic properties of PAM gels throughout the post-polymerization swelling process until equilibrium. First, local and global elastic properties (measured by rheology), were obtained during polymerization in the absence of swelling, and showed good agreement with each other. Four PAM hydrogel compositions were characterized thus, with corresponding storage shear moduli of 4530 Pa (termed stiffest), 2900 Pa (stiff), 538 Pa (soft) and 260 Pa (softest). Next, all compositions were subjected to swelling in phosphate buffered saline. Swelling ratios and local elastic moduli were measured at 0, 3, 6, 9, 12 and 24 hours post-polymerization for the soft and softest compositions, and once daily till 6 days post-polymerization for all four compositions. For the stiffest and stiff gels, swelling ratio and local elastic modulus changed negligibly with time, while for the soft and softest gels, substantial changes between Day 0 and Day 1 were found for both swelling ratio (increased by 21.6 % and 133 % , respectively) and local elastic modulus decreased (by 33.7 % and 33.3 %, respectively) substantially. Experimental data were analyzed by a model that combined ideal elastomer mechanics and poroelastic swelling kinetics model. Model predictions confirmed the validity of present measurements with respect to past studies where swelling and elastic properties were not measured simultaneously. The present study underlines the important effect swelling can have on PAM elastic properties and provides detailed quantitative data to guide the duration taken to reach equilibrium – a useful information for cell mechanics experiments. In addition, the simultaneous measurements of swelling and local elastic moduli provide novel data for the validation of theoretical models.